Protest tourism as gendered experience: constraints, feelings and gender roles of female activists - Tominaga, Kyoko (Frontiers in Sustainable Tourism, 2023)
This paper investigates protest tourism as a gendered experience. Recently, scholars have shown increasing interest in protest tourism, but they have mainly focused on the participants' motivation, emotions, and identity. Understanding gender differences in protest tourism is important in the investigation of both protests and tourism. This study discusses Japanese female protest tourism, focusing on three aspects: constraints, feelings and gender roles. Previous studies on tourism and social movements provide a research framework for these three aspects. Based on writings described by female activists and on interviews with participants, the paper reports three key findings. First, female participants face constraints when taking part in protest tourism due to domestic responsibilities and resource limitations. Second, women's protest tourists have fears about the risks of harassment and violence and are uncomfortable being in a marginalized position. Third, they are forced into a feminine role in demonstration speeches and accommodations; however, if they ignore social norms, they can liberate themselves from that role. These findings demonstrate the discouragement factors associated with protest tourism, namely its danger, one-time nature and uniqueness, by focusing on the marginalized actor. The discussion of the concept of protest tourism therefore includes a wider range of behaviors.